2010
DOI: 10.1590/s0103-64402010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Fingernail may not be a reliable biomarker of fluoride body burden from dentifrice

Abstract: Fingernail has been suggested as a biomarker of fluoride (F) body burden, but there is no consensus if it would be a reliable indicator of F exposure from dentifrice. Therefore, the present study was conducted to investigate if fingernails would have sensitivity to detect F exposure from dentifrice in young children. Twenty-three 1-3-year-old children living in the city of Piracicaba (0.72 ppm F in water), Brazil, were enrolled in two phases of different F exposure: in phase A (1st to 11th week), they were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The levels of F − in fingernails measured up to 34 mg/Kg in this study are among the highest reported in the literature, which mostly addressed low-F − cases of fluoridated water, salt, milk, and toothpaste exposure (e.g., Whitford et al, 1999; Levy et al, 2004; Pessan et al, 2005; Buzalaf et al, 2006 and 2011; de Almeida et al, 2007; Lima-Arsati et al, 2010). To our best knowledge, no population-based studies are available from regions of endemic exposure linking the F − concentrations in fingernail clippings to EF (or SF).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The levels of F − in fingernails measured up to 34 mg/Kg in this study are among the highest reported in the literature, which mostly addressed low-F − cases of fluoridated water, salt, milk, and toothpaste exposure (e.g., Whitford et al, 1999; Levy et al, 2004; Pessan et al, 2005; Buzalaf et al, 2006 and 2011; de Almeida et al, 2007; Lima-Arsati et al, 2010). To our best knowledge, no population-based studies are available from regions of endemic exposure linking the F − concentrations in fingernail clippings to EF (or SF).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, once F − is incorporated into nail at growth end, it will be unaffected by more recent F − intake and physiological variables (Whitford, 2005). Fingernail analysis of F − has previously been used to assess low-level exposures in communities with fluoridation of water, tooth paste, salt, and milk use (e.g., Buzalaf et al, 2011; Lima-Arsati et al, 2010; de Almeida et al, 2007; Buzalaf et al, 2006; Pessan et al, 2005; Levy et al, 2004; Whitford et al, 1999), but epidemiological studies that evaluate the suitability and sensitivity of this biomarker in populations with endemic fluorosis are virtually absent.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis over time seems to be an important factor for the verification of dose–response because data might vary (Figs and ) and there was one study did not identify the effect of fluoride intake from toothpaste . This suggests that studies comparing different fluoride concentrations must be conducted over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, care must be taken, since excessive exposure to fluoride by water consumption combined with other fluoride sources may result in undesirable effects, such as dental fluorosis (7)(8)(9). To achieve the expected results with this preventive method, a strict control of the process of water fluoridation is required, avoiding the undesirable effects of over-dosage, as well as avoiding underdosage, which does not offer the maximum benefits (2).…”
Section: Introductionmentioning
confidence: 99%